Strategi Manajerial Kepala Sekolah dalam Menjembatani Humanisme dan Digitalisasi di Era Merdeka Belajar (Studi di SMPN 4 Bataguh) - Azizah, Nor; Noviani, Widy; Madina, Maya; Hairullah, Hairullah; Suriansyah, Ahmad; Purwanti, Ratna (Adaara: Jurnal Manajemen Pendidikan Islam, 2025)
Entering the era of Society 5.0, the world of education is required to be able to integrate technological advances with humanistic values ​​in order to create a more inclusive and adaptive learning ecosystem. This study aims to explore the principal's leadership strategy in developing a humanistic educational approach integrated with digital technology at SMPN 4 Bataguh. Using a descriptive qualitative approach, data were collected through observation, in-depth interviews, and documentation studies. The results of the study indicate that the principal plays a central role as an agent of change, who not only directs the use of technology in learning, but also ensures the integration of ethical values, empathy, and character in every aspect of teaching and learning activities. The strategies implemented include developing a digital-based leadership vision, strengthening digital culture in schools, and ongoing training for teachers. These findings confirm that visionary and adaptive leadership is key to building education that is relevant to the demands of the 21st century and remains based on human values.